Chemical constituents and antibacterial activity of essential oils in Amomum longiligulare from Vietnam - N. Hung; N. H. Toan (Труды по прикладной ботанике, генетике и селекции)
This paper reports the chemical constituents and the antibacterial activity of essential oils from the leaves, rhizomes, and fruits of Amomum longiligulare T.L. Wu (Zingiberaceae) obtained by microwave-assisted hydrodistillation. The essential oils were analyzed by gas chromatography–mass spectrometry techniques. The minimum inhibitory concentration (MIC) values were measured by the broth microdilution assay. The oil yields of leaves, rhizomes and fruits from A. longiligulare were 0.23%, 0.27% and 1.93% (v/w), respectively, calculated on a dry weight basis. The leaf essential oil comprised mainly α-humulene (28.4%), α-pinene (24.9%), β-caryophyllene (17.3%), humulene epoxide II (7.3%), and β-pinene (4.7%). The major compounds of the rhizome essential oil were β-caryophyllene (28.7%), bicyclogermacrene (17.1%), humulene epoxide II (10.5%), camphene (7.9%), and α-pinene (5.7%). Camphor (40.7%) and bornyl acetate (34.2%) were the main constituents of the fruit oil. The essential oils demonstrated antimicrobial activities against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa with the MIC values ranging from 200 to 400 μg/mL. In summary, the A. longiligulare essential oils are a source of promising antibacterial agents. This is the first report on the chemical composition and antibacterial activity of A. longiligulare essential oil obtained by microwave-assisted hydrodistillation.